Caminhos da alfabetização em Minas Gerais: um olhar etnográfico para o ciclo inicial de alfabetização - Flavia Helena Pontes Carneiro (2006)
This research analyzes literacy and writing practices developed within the beginning of the educational reform in First Grade Literacy groups. The reform establishes a nine-year-long Elementary School in the state of Minas Gerais. The theoretic and methodological background to this case study is the interactive ethnographic approach. Data collecting involved continuous observation of activities in a First Grade Literacy group from a state public school in the outskirts of the city of Belo Horizonte. The qualitative research included a long period of classroom observation; videotapes; field notes; reproduction of artifacts such as notebooks, home works, memorandums, and exams; teachers meetings observation; and interviews with students, teachers and experts. In this new political educational context, the study acknowledged the importance of: 1. The association process between students of First Grade Literacy groups and its consequences for the (de) formation of the results produced in classroom by teachers and students. The analysis of different parties studied in a 4-month period examined the framework and criteria of student knowledge regarding reading and writing, which grounded the formation of new classes. 2. The study showed reading and writing practices developed after every new association in the First Grade Literacy group observed. 3. Finally, the study has demonstrated that both these aspects the association process and reading and writing practices are results of the networking of historical, political and social aspects from different institutional backgrounds.